2012
DOI: 10.1371/journal.pone.0029824
|View full text |Cite
|
Sign up to set email alerts
|

Integration of DNA Copy Number Alterations and Transcriptional Expression Analysis in Human Gastric Cancer

Abstract: BackgroundGenomic instability with frequent DNA copy number alterations is one of the key hallmarks of carcinogenesis. The chromosomal regions with frequent DNA copy number gain and loss in human gastric cancer are still poorly defined. It remains unknown how the DNA copy number variations contributes to the changes of gene expression profiles, especially on the global level.Principal FindingsWe analyzed DNA copy number alterations in 64 human gastric cancer samples and 8 gastric cancer cell lines using bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 49 publications
3
46
0
Order By: Relevance
“…Recently, some miRNAs were demonstrated to reduce AEG-1 expression. For instance, miR-375 could target AEG-1 to stimulate G1 arrest and apoptosis, and inhibit cell migration and invasion in head and neck cancer (Hui et al, 2011), and HCC (Fan et al, 2012); miR-136 triggered apoptosis partially by targeting AEG-1 in human glioma (Yang et al, 2012); and miR-26a was found to negatively regulate AEG-1 to enhance apoptosis in breast cancer (Zhang et al, 2011). Previous study reported that AEG-1 expression displayed increasing trend from normal liver tissue to hepatitis B and HBV-related HCC samples (Gong et al, 2012), which suggests that HBV may be involved in augmenting AEG-1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some miRNAs were demonstrated to reduce AEG-1 expression. For instance, miR-375 could target AEG-1 to stimulate G1 arrest and apoptosis, and inhibit cell migration and invasion in head and neck cancer (Hui et al, 2011), and HCC (Fan et al, 2012); miR-136 triggered apoptosis partially by targeting AEG-1 in human glioma (Yang et al, 2012); and miR-26a was found to negatively regulate AEG-1 to enhance apoptosis in breast cancer (Zhang et al, 2011). Previous study reported that AEG-1 expression displayed increasing trend from normal liver tissue to hepatitis B and HBV-related HCC samples (Gong et al, 2012), which suggests that HBV may be involved in augmenting AEG-1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,7 A recent study also revealed that 20q12-q13.3 is the most frequently amplified region in gastric cancer. 42 Several genes located at this locus, such as AIB1 and BCAS1, have been shown to be involved in growth and aggressiveness of human cancers. 43,44 However, biological functions of putative tumor-promoting genes in this region have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding that in all GC samples there were at least two RUNX3-specific FISH signals per cell [19] indicates that there is no loss of RUNX3 in GC but rather amplification of regions encompassing the chromosome 1 centromere [19]. Furthermore, two recent high-resolution comparative genomic hybridization (CGH) studies of GC biopsies one involving 193 patients and the other 64 patients, revealed that the chromosome 1p36 region, which harbors RUNX3, was not frequently deleted in GC [73,74]. The genomic regions that were recurrently deleted in GC harbored various known TSGs, while the frequently amplified ones housed known oncogenes [73] (Table 4).…”
Section: Cancer Mutations and Genome-wide Association Studies (Gwas) mentioning
confidence: 99%